INNOVATION AND TRADITION IN REISMARQUES PAINTING - Monica Cauhi Wanderley (Travessias, 2009)
If you stop to observe the current art scene, we see that contemporary art has reached an intense variety of creative possibilities. However, the variety of creative possibilities are not always unprecedented boom, because contemporary art has also in the past a strong source of inspiration. Thus, tradition and innovation mingle in the art work, allowing the (watchful) eyewitness the assessment of an innovation of the past. So, this research is intended to reflect the presence of tradition on the painting of the contemporary artist Reismarques, discussing the tradition of innovation in topics such as composition, subject and artist and viewer